THE EFFECTS OF HIGH-FAT, LOW-FAT, AND SUCROSE-FREE DIETS ON MICE WITH INNATE IMMUNE MEDIATED COLITIS. (22nd January 2022) - Ruley-Haase, Katelyn; Boger-May, Antonia; Huerta, Alvaro Torres; Boone, David; Reed, Theodore; Rajashekara, Arpitha Mysore; Pederson, Cameron; Omoijuanfo, Ese-Onosen; Scmidt, Annie Cate
Abstract: While the cause of Inflammatory bowel disease (IBD) is unknown, certain symptoms may be altered by a multitude of factors including genetics, lifestyle choices, and diet choices. High fat diets (HFDs) are diets with fat accounting for ≥20% of total caloric intake. These diets are known risk factors for IBD onset and worsening symptoms. Mice which overexpress the NF-kB inhibitor TNFAIP3 (A20) were crossed with RAG1 -/- mice. These A20 x RAG1 -/- (TRAG) mice develop 100% penetrant colitis by eight weeks of age which is not observed in A20 or RAG1 -/- littermates. This study examined the effects of a 45% Kcal from fat diet (Research Diets D12451), 10% Kcal fat or "low fat" diet (LFD; Research Diets D12450H), and 10% Kcal fat with cornstarch and maltodextrin for carbohydrates instead of sucrose or "no sucrose" diet (NSD; Research Diets D12450K) on TRAG mice, focusing on changes in inflammation histologically, the gut microbiome, blood glucose, and fat content. All diets were matched for carbohydrates, proteins, and micronutrients. Diets were irradiated to prevent outside bacterial exposure. HFDs have been implicated in worsening colitis symptoms in clinical studies, but no such studies have been completed using the TRAG model of colitis. Four-week-old mice consumed these non-standard chows for four weeks and were humanely euthanized at eight weeks. Severity of colitis was assessed histologically, and changes in the microbiome were assessed via rRNA sequencing. Male and female mice experienced greater weight gain over time on the HFD compared to mice on the LFD (male p=0.0007, female p=0.002) and NSD (male p=0.005, female p=0.003). No significant difference in food consumption was observed in male or female mice on any of the three diets. Both male and female mice had higher blood glucose levels on the HFD than on the LFD and NSD. Male and female mice also had shorter colon lengths on the HFD compared to the LFD and NSD. Male mice on the HFD showed a significant increase in IG and PG weights p=0.0095 and p=0.0015, respectively), as well as liver weights (p=0.005). Female mice also saw a significant increase in PG weight when consuming the HFD relative to the LFD (p=0.045), but no significant difference was observed between the HFD and NSD. This investigation suggests that diets high in fat may worsen colitis symptoms such as inflammation and shortened colon length. HFDs may also increase WAT throughout the body, including in the liver, particularly in males. For future studies TRAG mice should be placed on the same diets for 8-12 weeks to see if results persist as mice age. In addition, TRAG mice could be placed on these diets starting at eight weeks of age to observe how HFDs alter colitis post-onset. Male and female sex differences should be noted, as it appears male mice have more significant changes in their overall WAT than females while consuming a HFD.